Frequency Reconfigurable Epsilon Negative Metamaterial Antenna - Arrauzah Razak; M. K. A. Rahim; H. A. Majid; N. A. Murad (International Journal of Electrical and Computer Engineering (IJECE), 2017)
This paper proposes metamaterial (MTM) inspired frequency reconfigurable antenna based on thecircular electric field coupled (ELC) resonator. It is composed of circular shape ELC resonator with the radius size of 7 mm. By inserting two switches between the gaps at both side of the circular ELC resonator, it is possible to switch ON or OFF the unit cell. The antenna has been simulated using CST Microwave Studio software tool. The simulation result shows that the proposed antenna is capable of reconfiguring between two different frequencies which are2.18 GHz and 2.64 GHz. The simulated bandwidth at -10 dB is 4.12 % at resonance frequency of 2.18 GHz and 8.7% at 2.64 GHz